Corrosion and mechanical properties of age‐hardened UNS N06625 forged bars for oil and gas applications. Issue 10 (12th April 2019) - Febbrari, Andrea; Gelfi, Marcello; Giovanardi, Roberto; Montesano, Lorenzo; Pola, Annalisa; Montani, Raimondo; Veronesi, Chiara; Cavagnola, Matteo
Abstract: UNS N06625 is a well‐known nickel‐base superalloy generally used in annealed condition due to its excellent corrosion resistance in the most severe environments containing sulfides and chlorides at high pressure and temperature. In general, the most efficient way to increase the alloy strength is by cold working, but obviously, this cannot be applied in case of large forgings. Actually, looking at its chemical composition, UNS N06625 can be considered an age‐hardenable material, whose mechanical strength can be improved by promoting the second phase γ″ precipitation in the matrix. The aim of this paper was to assess the achievable mechanical properties and corrosion resistance of UNS N06625 forged bars in age‐hardened condition with respect to the annealed one, to understand the feasibility of this not conventional heat treatment for the industrial application. Abstract : The aim of this paper was to assess the achievable mechanical properties and corrosion resistance of UNS N06625 forged bars in age‐hardened condition with respect to the annealed one, to understand the feasibility of this not conventional heat treatment for the industrial application.